Décollements, Detachments, and Rafts in the Extended Crust of Dangerous Ground, South China Sea: The Role of Inherited Contacts. Issue 6 (12th June 2019) - Liang, Yao; Delescluse, Matthias; Qiu, Yan; Pubellier, Manuel; Chamot‐Rooke, Nicolas; Wang, Jun; Nie, Xie; Watremez, Louise; Chang, Sung‐Ping; Pichot, Thibaud; Savva, Dimitri; Meresse, Florian
Abstract: We investigate the crustal structure of the Dangerous Ground (South China Sea) through processing and interpretation of coincident wide‐angle reflection and refraction seismic data. Continental crust of Dangerous Ground has been moderately thinned, down to 15 km, so that most of the structures accompanying the early opening of the South China Sea from Cretaceous to Miocene have been preserved. Subbasement reflectors as well as refraction velocities image an interpreted dismantled Mesozoic metamorphic unit in the southernmost section of our study area. A rollover structure indicates that the reflective base of the unit was used as a décollement where low‐angle normal faults root and blocks rafted. The metamorphic unit is discontinued in a nearby basin located immediately to the north, where the refraction velocity model shows thinning of the crust from 20 to 15 km, with the presence of a 5‐km‐high mantle dome. In this deeper basin, mass transport deposits are found lying on a strong amplitude basement reflector interpreted as the footwall of an 15 km offset crustal detachment surface that we link down to the mantle dome. We infer that the detachment reactivated an inherited low‐angle contact most probably related to the Yanshanian belt. In map view, the reactivated structure forms a half‐graben basin oriented NNE‐SSW oblique to the generally accepted direction of extension. This orientation follows the general trend of a granitic belt that spanned the South China margin prior to extension, related to the subduction of the Paleo‐Pacific. Key Points: We investigate the crustal structure of the Dangerous Ground, southern South China Sea, using multichannel and refraction seismic data Extensional deformation localizes on a 10–15‐km offset crustal detachment thinning the crust from 20 to 15 km The detachment activity was a breakup propagation attempt along a reactivated contact bounding Mesozoic, arc‐related granitic plutons